Spatial Response Uniformity of Silicon–Based CdS and PbS Heterojunction Laser Detectors - Ismail, Raid A.; . A. Sultan, Omar A; Jasim, Sa’ad Y. (Iraqi Journal of Laser, 2002)
This paper demonstrates the spatial response uniformity (SRU) of two types of heterojunctions (CdS, PbS /Si) laser detectors. The spatial response nonuniformity of these heterojunctions is not significant and it is negligible in comparison with p+- n silicon photodiode. Experimental results show that the uniformity of CdS /Si is better than that of PbS /Si heterojunction